LEGAL LOOPHOLES THAT ALLOW ACQUISITION IN COMPANIES - Hamid Abed, Andalus; Rahi Naser, Raheem (International Journal of Psychosocial Rehabilitation, 2020)
As interested researchers, we ought to diagnose the legal loopholes in companies that allow acquisition, whether in the same company or among different companies within our field of study. This is necessary to obtain suitable solutions for the lawmakers and to be included in a legal text that covers these loopholes in the law, for instance, the Iraqi Companies Act No. 21, 1997 (edited). This subject is broached in three sections: the first section discusses the number of votes the corporations possess and their representation by others. The second section broaches the mock writing and its conditions, while the third section studies the waiver of the right to vote and fraudulent ways of some corporations to obtain votes. In this way, through extrapolation of legal texts and doctrinal teachings, several legal loopholes that allow the acquisition of some companies with respect to others or that possibly encourage the emergent of acquisition activity have been identified.